Ontogenetic instars of Melanozetes paramollicomus sp. nov., with remarks on morphological ontogeny of Sphaerozetinae (Acari: Oribatida: Ceratozetidae) - Bayartogtokh, Badamdorj; Ermilov, Sergey G.; Shtanchaeva, Umukusum Ya.; Subías, Luis S. (Zootaxa, 2021)
Although the juvenile instars of oribatid mite subfamily Sphaerozetinae is well known compared to the other subfamilies of Ceratozetidae (Ceratozetinae and Trichoribatinae), information on morphological ontogeny of some species is still incomplete. Herein, Melanozetes paramollicomus sp. nov. is proposed from Ethiopia, based on adult and juvenile instars. Additionally, comparative analysis of ontogenetic instars of species belonging various genera of Sphaerozetinae with known juveniles, is given, and the major characteristics of juvenile instars of 20 species are presented.